Cases on technologies for teaching criminology and victimology methodologies and practices - Sette, Raffaella (Information Science Reference, 2010)
"This book is for those involved in the planning, development and implementation of different teaching methodologies of criminology and victimology in the academic field, in the police academies and in victim support services"--Provided by publisher.